2016
DOI: 10.1007/s00246-016-1440-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Central Aortic Pressure Levels, Wave Components and Determinants Associated with High Peripheral Blood Pressure States in Childhood: Analysis of Hypertensive Phenotype

Abstract: The aims were to determine whether children's high peripheral blood pressure states (HBP) are associated with increased central aortic blood pressure (BP) and to characterize hemodynamic and vascular changes associated with HBP in terms of changes in cardiac output (stroke volume, SV), arterial stiffness (aortic pulse wave velocity, PWV), peripheral vascular resistances (PVR) and net and relative contributions of reflected waves to the aortic pulse amplitude. We included 154 subjects (mean age 11; range 4-16 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 44 publications
1
39
0
1
Order By: Relevance
“…The ENIGMA study [ 16 ••] reported AIx to be significantly lower in young adults with ISH, compared to control group. Other studies [ 25 ••, 32 , 51 ••] have reported no significant difference in AIx between hypertensive and control children and adolescents. A more direct measure of reflection is the reflection coefficient, obtained by mathematical separation of forward and backward waves (from pressure and flow), as the ratio of the amplitude of the backward to forward wave.…”
Section: Determinants Of the Pulsatile Component Of Bpmentioning
confidence: 87%
“…The ENIGMA study [ 16 ••] reported AIx to be significantly lower in young adults with ISH, compared to control group. Other studies [ 25 ••, 32 , 51 ••] have reported no significant difference in AIx between hypertensive and control children and adolescents. A more direct measure of reflection is the reflection coefficient, obtained by mathematical separation of forward and backward waves (from pressure and flow), as the ratio of the amplitude of the backward to forward wave.…”
Section: Determinants Of the Pulsatile Component Of Bpmentioning
confidence: 87%
“…Otherwise, AS and arrival time and amplitude of wave reflections are the main determinants of cSBP and cPP, while peripheral vascular resistances and cardiac output are the main determinants of MBP and cDBP. In this context, it is important to emphasize that simultaneous measurements of central (aortic) BP and cAIx (using a single device) in children and adolescents allow us not only to know if cSBP and cPP are within physiological levels, but also in case of abnormal values to realize if they were associated or not with increased wave reflection levels (cAIx) [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 Therefore, pulse pressure (PP), which the difference between SysP and DiaP, increases in the peripheral arteries; for example, between the root of the aorta and the brachial artery, PP is amplified by around 14 mmHg. [12][13][14] This is a physiological finding known as PP amplification ( Figure 2).…”
Section: Arterial Stiffness Indexesmentioning
confidence: 91%
“…This phenomenon is known as pulse pressure amplification and is calculated by dividing systolic pressure central (SysPc) by peripheral systolic pressure (SysPp). Adapted from García-Espinosa et al 14 occur in any segment in which there is discontinuity of flow, such as at bifurcations and, primarily, when the incident waves reach the peripheral arteries with greater resistance and lower elasticity. Thus, to aid understanding, the waves can be designated as the incident wave (or ejection wave) and the reflected wave and the resulting pulse wave is the sum of the incident wave and the reflected wave ( Figure 3).…”
Section: Arterial Stiffness Indexesmentioning
confidence: 99%
See 1 more Smart Citation